Early tracheostomy in ventilated stroke patients: Study protocol of the international multicentre randomized trial SETPOINT2 (Stroke-related Early Tracheostomy vs. Prolonged Orotracheal Intubation in Neurocritical care Trial 2). Issue 3 (April 2016) - Schönenberger, Silvia; Niesen, Wolf-Dirk; Fuhrer, Hannah; Bauza, Colleen; Klose, Christina; Kieser, Meinhard; Suarez, José I; Seder, David B; Bösel, Julian; ,
Background: Tracheostomy is a common procedure in long-term ventilated critical care patients and frequently necessary in those with severe stroke. The optimal timing for tracheostomy is still unknown, and it is controversial whether early tracheostomy impacts upon functional outcome. Method: The Stroke-related Early Tracheostomy vs. Prolonged Orotracheal Intubation in Neurocritical care Trial 2 (SETPOINT2) is a multicentre, prospective, randomized, open-blinded endpoint (PROBE-design) trial. Patients with acute ischemic stroke, intracerebral hemorrhage or subarachnoid hemorrhage who are so severely affected that two weeks of ventilation are presumed necessary based on a prediction score are eligible. It is intended to enroll 190 patients per group (n = 380). Patients are randomized to either percutaneous tracheostomy within the first five days after intubation or to ongoing orotracheal intubation with consecutive weaning and extubation and, if the latter failed, to percutaneous tracheostomy from day 10 after intubation. The primary endpoint is functional outcome defined by the modified Rankin Scale (mRS, 0–4 (favorable) vs. 5 + 6 (unfavorable)) after six months; secondary endpoints are mortality and cause of mortality during intensive care unit-stay and within six months from admission, intensive care unit-length of stay, duration of sedation, duration of ventilation and weaning, timing and reasons for withdrawal of life support measures, relevant intracranial pressure rises before and after tracheostomy. Conclusion: The necessity and optimal timing of tracheostomy in ventilated stroke patients need to be identified. SETPOINT2 should clarify whether benefits in functional outcome can be achieved by early tracheostomy in these patients.